Upper lobe preservation is not a challenge - Maurizi, Giulio; Marinucci, Beatrice Trabalza; Rendina, Erino Angelo (Journal of Thoracic Disease, 2019)
We have particularly appreciated the interesting letter from Cohen and colleagues (1) with their comments about our recent paper (2). They underline the importance of the use of lung-sparing operations for the treatment of NSCLC in order to avoid pneumonectomy. In particular, the latter authors confirm our suggestion that even a particular and challenging-considered operation such as lower sleeve lobectomy can provide good short and long term results (3-6). In our study (2), we stressed the aspect that left lower sleeve lobectomy and right lower bilobectomy should have been considered as a peculiar subset among sleeve resections in order to better investigate the outcome after this kind of reconstructive operations that, up to our paper, were usually included as very small number in wider series of bronchial and bronchovascular reconstruction patients.